Role of Scaffold Protein Proline-, Glutamic Acid-, and Leucine-Rich Protein 1 (PELP1) in the Modulation of Adrenocortical Cancer Cell Growth - Arianna De Luca; Paola Avena; Rosa Sirianni; Adele Chimento; Francesco Fallo; Catia Pilon; Ivan Casaburi; Vincenzo Pezzi (Cells, 2017)
PELP1 acts as an estrogen receptor (ER) coactivator that exerts an essential role in the ER’s functions. ER coregulators have a critical role in the progression and response to hormonal treatment of estrogen-dependent tumors. We previously demonstrated that, in adrenocortical carcinoma (ACC), ERα is upregulated and that estradiol activates the IGF-II/IGF1R signaling pathways defining the role of this functional cross-talk in H295R ACC cell proliferation. The aim of this study was to determine if PELP1 is expressed in ACC and may play a role in promoting the interaction between ERα and IGF1R allowing the activation of pathways important for ACC cell growth. The expression of PELP1 was detected by Western blot analysis in ACC tissues and in H295R cells. H295R cell proliferation decrease was assessed by A3-(4,5-Dimethylthiaoly)-2,5-diphenyltetrazolium bromide (MTT) assay and [3H] thymidine incorporation. PELP1 is expressed in ACC tissues and in H295R cells. Moreover, treatment of H295R with E2 or IGF-II induced a multiprotein complex formation consisting of PELP1, IGF1R, ERα, and Src that is involved in ERK1/2 rapid activation. PELP1/ER/IGF1R/c-Src complex identification as part of E2- and IGF-II-dependent signaling in ACC suggests PELP1 is a novel and more efficient potential target to reduce ACC growth.